What does Ainu cultural revitalisation mean to Ainu and Wajin youth in the 21st century? Case study of Urespa as a place to learn Ainu culture in the city of Sapporo, Japan. (June 2019) - Uzawa, Kanako
This article illustrates living experiences of Ainu cultural practices by the students of Urespa. Urespa is a self-motivated, non-profit social initiative or association founded in 2010 by Professor Honda Yuko at Sapporo University with the aim of bringing Ainu and Wajin students together in a curriculum-based environment to co-learn the Ainu language and Ainu cultural practices. In the Ainu language, urespa means "growing together". The article draws on the author's fieldwork with Urespa in Sapporo, Hokkaido, in 2016 in focusing on a new way of practising Ainu culture in an urban setting in the 21st century. The article, therefore, focuses on Ainu cultural revitalisation, everyday cultural practices, and on how it plays out within Urespa in a context of decolonisation and self-determination in Japan.